2021
DOI: 10.1108/ijchm-06-2020-0576
|View full text |Cite
|
Sign up to set email alerts
|

Listening to your employees: analyzing opinions from online reviews of hotel companies

Abstract: Purpose This study aims to examine the factors influencing hotel employee satisfaction and explores the different sentiments expressed in these factors in online reviews by hotel type (premium versus economy) and employment status (current versus former). Design/methodology/approach A total of 78,535 online reviews by employees of 29 hotel companies for the period of 2011-2019 were scraped from Indeed.com. Structural topic modeling (STM) and sentiment analysis were used to extract topics influencing employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…However, no studies, to the best of our knowledge, have attempted to examine how LoS can affect the review-posting behaviors of consumers. Recently, many studies on online reviews in tourism examined factors influencing online review and how they influence hotel strategies and other consumers; however, no studies investigated the relationship between LoS and online reviews (Bortoluzzi et al , 2020; Filieri et al , 2021; Gour et al , 2021; Liu and Hu, 2021; Mariani and Borghi, 2021; Shi and Chen, 2021). The current study examined how different LoS systematically influence consumer review-posting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies, to the best of our knowledge, have attempted to examine how LoS can affect the review-posting behaviors of consumers. Recently, many studies on online reviews in tourism examined factors influencing online review and how they influence hotel strategies and other consumers; however, no studies investigated the relationship between LoS and online reviews (Bortoluzzi et al , 2020; Filieri et al , 2021; Gour et al , 2021; Liu and Hu, 2021; Mariani and Borghi, 2021; Shi and Chen, 2021). The current study examined how different LoS systematically influence consumer review-posting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Closed-form evaluations usually only allow employees to score their overall opinion of their company on a five-point scale. These evaluations not only reflect the company’s internal service quality (Chen, 2021) but also predict customer satisfaction and re-patronage intentions, and can accurately predict the company’s financial performance. For example, Fang et al (2021) found a significant correlation between closed-form evaluations and company stock returns, and that higher ratings were associated with higher return on assets, profit margin and asset turnover.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The value of the information in open-ended comments has been verified. For example, Chen (2021) discovered that workplace bullying and dirty work, organizational support and career advancement as significant antecedents of hotel employees’ satisfaction. Additionally, employees of premium hotels expressed more positive emotions in their open-ended comments compared to those from budget hotels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, smart technology can help human resources (HR) managers to optimise HR, both strategically and operationally, by facilitating rota management; compensation data; recruitment, and onboarding, in collaboration with external agencies, hotel schools and recruitment companies. Smart hospitality also enables a constant flow of relevant employee performance data (Ahmad and Scott, 2019) and assists in evaluating employee satisfaction, through monitoring social media (Shi and Chen, 2021).…”
Section: Smart Hospitality Stakeholders: Reengineering Value Chains A...mentioning
confidence: 99%